The power of the industrial product lobby: controversy, doubt, contradiction, lies and deceit and attacks on the Ramazzini Institute - Mehlman, Myron A. (European Journal of Oncology and Environmental Health, 2009)
Over the years, industry and industry-paid consultants have provided studies that show that their chemicals are safe. Efforts include use of laboratories such as the Industrial Biotest Laboratory that were shown in 1976 to have falsified experimental data to the Shanghai Health Study proposed and funded by the petroleum industry to prove that benzene exposure is not harmful and benzene is non-carcinogenic. Studies reported by industry consultants have been reevaluated by independent scientists, and flaws in data collection or data analysis have been published. Industry has long attempted to mischaracterize studies by the Ramazzini Foundation (RF), founded by Cesare Maltoni (deceased). Through the 1970’s to the present time, the RF has been scrutinized by governmental regulatory bodies, studies have been duplicated by the National Toxicology Program, and studies reported by the RF have been consistently found to be accurate. Recently, industry has attempted to refute RF animal studies of aspartame and MTBE that show increases in lymphohematological neoplasms by stating that animals are afflicted with bacterial infections that cause inflammation that resembles neoplasms. RF data and slides that address this point, as well as repeated statistical analysis of RF data, show that this is not so. The data stand.